Ritual Penusur Sira dan Dokan Arts Festival sebagai Daya Tarik Eisata di Desa Dokan, Kabupaten Karo, Sumatera Utara - Rimba, Fellix (Universitas Sebelas Maret, 2024)
This study aims to determine the ritual of Penusur sira in the tradition of the Dokan village community as an adaptation to the environment, to find out the shape of the Siwaluh Jabu traditional house that adapts to natural conditions and to know the appearance of the Dokan Art Festival in preserving and introducing local culture. This research uses a descriptive method with a qualitative approach with socio-cultural observations of the community to answer the research objectives. The results of the study show that the ritual of the ancestor sira and the traditional house of Siwaluh Jabu are local wisdom that must be maintained and preserved so that they do not become extinct along with the times. The Karo community and several art activists innovated to introduce Dokan village by holding a Dokan Art Festival. This is in addition to maintaining the existence of local culture but also becomes an attraction for tourists by presenting performances that tell the history and entertainment of local music and dances.